PENGARUH KOMPENSASI FINANSIAL TERHADAP MOTIVASI KERJA KARYAWAN MIE CELOR H.M. SYAFEI PALEMBANG - Rumenda, Helmi (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study aims to determine the effect of financial compensation on work motivation of Mie Celor H.M. employees Syafei Palembang. To create work motivation, it is certainly necessary to provide a driving force to create one's work enthusiasm so as to achieve high morale. There are many factors that affect employee work motivation, including financial compensation in accordance with the work that has been done. In this study, the financial compensation variable is an independent variable and work motivation as the dependent variable. Data collection techniques were carried out using interviews, questionnaires, and literature study. The questionnaire submitted refers to the Likert scale. The data instrument test was carried out with the Data Validity Test with the results of all question items being declared valid and the Reliability Test with the results of all question items being Reliable. Hypothesis testing uses simple regression analysis through the t-test, with a view to knowing the effect of the independent variable on the 95% dependent variable (a = 0.05). T-test (partially) on the variable of financial compensation (X) obtained tcount (3.840) ˃ ttable (2.060), based on hypothesis testing means that work motivation (Y) is influenced by financial compensation.